Implications of pulse wave velocity and central pulse pressure in heart failure with reduced ejection fraction - Anette Caroline Kõre; Tuuli Joonsalu; Martin Serg; Priit Pauklin; Jüri Voitk; Indrek Roose; Jaan Eha; Priit Kampus (Blood Pressure)
Background Carotid-femoral pulse wave velocity (cfPWV) and central pulse pressure (PP) are recognised as significant indicators of vascular health and predictors of cardiovascular outcomes. In this study, associations between central hemodynamics and left ventricular (LV) echocardiographic parameters were investigated in subjects with heart failure with reduced ejection fraction (HFrEF), comparing the results to healthy individuals.Methods and results This cross-sectional prospective controlled study included 50 subjects with HFrEF [mean LV ejection fraction (EF) 26 ± 6.5%] and 30 healthy controls (mean LVEF 65.9 ± 5.3%). Pulse wave analysis (PWA) and carotid-femoral pulse wave velocity (cfPWV) were used to measure central hemodynamics and arterial stiffness. The HFrEF group displayed higher cfPWV (8.2 vs. 7.2 m/s, p = 0.007) and lower central (111.3 vs. 121.7 mmHg, p = 0.001) and peripheral (120.1 vs. 131.5 mmHg, p = 0.002) systolic blood pressure. Central pulse pressure (PP) was comparable between the two groups (37.6 vs. 40.4 mmHg, p = 0.169). In the HFrEF group, cfPWV significantly correlated with left ventricular end-diastolic volume (LVEDV) index (mL/m2) and LVEF, with LVEDV index being a significant independent predictor of cfPWV (R2 = 0.42, p = 0.003). Central PP was significantly associated with heart rate, LVEF and LVEDV index, with the latter being a significant independent predictor of central PP (R2 = 0.41, p < 0.001). These correlations were not observed in healthy controls.Conclusions Significant associations between central hemodynamic measures and LV echocardiographic parameters were identified, suggesting the potential to use PWA and cfPWV as possible tools for managing HFrEF.